Magnetic and structure properties of Cd doping Bi-2223 superconductor - SE Mousavi Ghahfarokhi; M Zargar Shoushtari (Iranian Journal of Physics Research, 2010)
In this paper, Bi1.64-xPb0.36CdxSr2Ca2Cu3Oy (BPCSCCO) superconductor with x = 0.0, 0.02, 0.04 and 0.06 is made by the solid state reaction method. The magnetic susceptibility measurements were performed using AC susceptometer. The microstructure and morphology of the samples have been studied by X-ray diffraction, scanning electron microscope and energy dispersive X-ray. The results show that the partial substitution of Pb for Bi in the Bi-based superconductor increases the volume fraction of Bi-2223 phase. We also found that by doping of Cd, the high Tc phase is promoted and stabilized in the Bi-Pb-Sr-Ca-Cu-O system. The results of the X-Ray diffraction patterns and magnetic susceptibility measurements show that the low amount of Cd and long annealing time enhance the fraction of Bi-2223 phase. The maximum value volume fraction of Bi-2223 phase for sample with annealing time of 270 hours and 0.04 of Cd doping is obtained